Foliar application of calcium and boron improves the spike fertily and yield of wheat (Bioscience Journal, 2016)
Foliar applications of calcium (Ca) and boron (B) could improve the fertilization of flowers and enhance the wheat yield. The effects of foliar spray of Ca and B on plant growth, grain yield and yield components of wheat were investigated in this study. Treatments consisted of 0, 1.8, 3.6, and 7.2 L ha-1 application of chelated fertilizer containing 125 g L-1 of Ca and 6 g L-1 of B (Omega Cabor II®), divided into two spray, the first one at tillering and the second at early bloom. The results revealed that foliar spray of Ca and B did not affect the stem diameter, peduncle length, spike length, hectoliter weight and thousand-grain mass of wheat. Maximum plant height and flag leaf insertion height was recorded with 4.0 L ha-1 application of foliar fertilizer (4% increase over control). The 7.2 L ha-1 application of foliar fertilizer increased significantly the number of spikelets per spike (9%), number of grains per spike (24%), grain mass per spike (28%), spike mass (14%), number of spikes m-2 (32%) and grain yield (30%) compared to the control. Foliar application of Ca and B improves growth, fertilization of flowers and the number of fertile tillers of wheat plants resulting in higher grain yield.